Alzheimer's Research & Therapy - Golde, Todd E.; Scheltens, Philip; Galasko, Douglas R.
Alzheimer's Research & Therapy is the major forum for translational research into Alzheimer's disease. An international peer-reviewed journal, it publishes open access basic research with a translational focus, as well as clinical trials, research into drug discovery and development, and epidemiologic studies. The journal also provides reviews, viewpoints, commentaries, debates and reports. Although the primary focus is Alzheimer's disease, the scope encompasses translational research into other neurodegenerative diseases.